The Effects Of Viral Marketing, Celebrity Endorser And Brand Association Toward Purchase Decision Of Ms Glow Skincare Products - Muhammad Fathur Rayhaan; Lamhot Henry Pasaribu (Institute of Computer Science (IOCS), 2022)
This study aims to see the influence generated by Viral Marketing, Celebrity Endorser and Brand Association on Purchase Decision of MS Glow skincare products. The method of collecting data that has been used in this research is by distribution of questionnaires to respondents using non-probability sampling technique. The data processing carried out in this research is by using Partial Least Squared – Structural Equation Modeling (PLS – SEM) using the help of the Smart PLS 3.3.3 program. The results obtained in the study indicate that 1) Viral Marketing does not have a positive effect on Purchase Decisions from consumers of MS Glow skincare products, 2) the next results state that Celebrity Endorser has a positive effect on Purchase Decisions of MS Glow skincare products and 3) the last result shows that Brand Association has a positive effect on Purchase Decision of MS Glow skincare products